Method of payment and risk mitigation in cross-border mergers and acquisitions - Huang, Peng; Officer, Micah S.; Powell, Ronan (Journal of Corporate Finance, 2016)
We argue that the method of payment in cross-border mergers and acquisitions (M&As) can mitigate country-level governance risk for the acquirer. We find a greater use of stock as the method of payment in cross-border deals involving targets from countries with high governance risk relative to that in the acquirer's country. This increased use of stock in riskier cross-border deals is consistent with the optimal reaction of the acquirer to avoid overpayment, even though we also show that the use of stock (instead of cash) as the method of payment in cross-border deals is associated with a lower likelihood of deal completion. Furthermore, for more recent periods (i.e., after 2000) we show that the use of stock (cash) has increased (decreased) significantly in cross-border deals, resulting in convergence with the method of payment used in domestic deals.